Keberlanjutan Agroindustri Penggilingan Padi Skala Besar di Kabupaten Subang, Jawa Barat - Dewi, Norma; Noor, Trisna Insan; Trimo, Lucyana (Analisis Kebijakan Pertanian, 2025)
Domestic rice production is the primary source of staple food availability. The rice milling business is the second largest source of rice stocks after those stored in households. From 2012-2020, the number of national rice milling businesses decreased from 182,199 units to 169,789 units or decreased by 6.81 percent. In the same period, large-scale rice milling businesses decreased by 49.11 percent, from 2,075 business units to 1,056 units. The research objective was to analyze the level of sustainability of large-scale rice milling in Subang Regency, West Java. The analytical method is the mixing method, and the analysis tool uses the MDS with the RAP-RICEMILL approach. The research results show that the ecological dimension has an index of 68.42 (quite sustainable), the economic dimension index of 67.71 (quite sustainable), the social dimension index of 48.34 (less sustainable), the technological dimension index 61.31 (quite sustainable), and the legal dimension and institutional index 59.94 (quite sustainable). The results of this study indicate that communication be carried out between the government and rice milling business actors to formulate policies that do not harm business actors, farmers, or consumers. In addition, it is necessary to activate rice milling associations in facilitating the development of milling businesses, utilizing by-products such as rice bran and husks to achieve higher economic value, expanding marketing networks, and developing partnerships with farmers for grain supply. Furthermore, rice mills need to increase capacity and use more modern technology to produce good-quality rice at low operating costs.
Keywords: food availability; RAP-Ricemill; sustainability; rice milling